DNAssist, a C++ Program for Editing and Analysis of Nucleic Acid and Protein Sequences on PC-Compatible Computers Running Windows 95, 98, NT4.0 or 2000. (June 2000) - Patterton, Hugh G.; Graves, Steven
The size of sequence databases, the rapid rate of generating sequence data and the need to routinely construct recombinant DNA molecules in molecular biological research necessitate the frequent handling and analysis of nucleotide and protein sequences on a computer. Although several console or Web-based utility programs are available, the application of these programs generally requires reformatting the data when proceeding from one such program to the next. The acquisition of elaborate, integrated program suites is financially prohibitive to smaller laboratories. Here, we report the development of DN Assist, a shareware program for editing and analysis of nucleic acid and protein sequences. It was developed as a multiple–document interface program—similar to a word processor– where sequences are entered, edited and analyzed in a single integrated environment. DN Assist can calculate the physicochemical properties of a sequence, convert between nucleic acid and protein sequences, translate DNA in multiple frames, identify open reading frames and locate ambiguous sequence patterns allowing gaps and mismatches. DN Assist also performs restriction enzyme and transcription factor—binding site analyses of DNA sequences, the multiple alignment of nucleic acid and protein sequences and the analysis of DNA sequences for nucleosome positioning sites.